If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (z) * 5 + -1 = 0 Reorder the terms for easier multiplication: 5z + -1 = 0 Reorder the terms: -1 + 5z = 0 Solving -1 + 5z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 5z = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 5z = 0 + 1 5z = 0 + 1 Combine like terms: 0 + 1 = 1 5z = 1 Divide each side by '5'. z = 0.2 Simplifying z = 0.2
| -67=6x-12+5x | | 4-6x=-4x-18 | | 3m+4n+6n= | | (1/3)h-4((2/3)h-3 | | m^3p^2q^10/m^-2p^4q^-6= | | 4-5x=3x+1 | | 40=1.69n | | -12-(-30)= | | 35-2x=x^2 | | 44x+2=45 | | 44/5÷11/4 | | 6x+9=27-2x | | 1/5=×/15 | | a=x^2-30x+225 | | A+-70=2 | | 4-5lnx=8 | | 12x^2-75x+85.25=0 | | Y=1x+13 | | 24x^2+36x^3= | | 7=4g-5 | | a=22 | | 3/8=y/5 | | 6-5x+6x=18 | | 6-5x+6=18 | | 2x^4-6x^3-128=0 | | 26=-4+5n | | y=10-6y | | 3a+5=-2a+24 | | 2x^4-6x^3=128 | | (8i)(5i)(6i)=x | | 3+3lnx=2 | | K+k+K+4(2k+6)+5k= |